(NiZBRANNOE (B/s - (NpASTERNAK(B, (NbORIS lEONIDOWI^s ((NmOSKWA(B:s (NmOLODAQ GWARDIQ(B,s, 1991)
(Nw KNIGU LAUREATA nOBELEWSKOJ PREMII bORISA pASTERNAKA WHODQT PROIZWEDENIQ(B: "(NwYSOKAQ BOLEZNX(B", "(NoHRANNAQ GRAMOTA(B", "(NsTIHOTWORENIQ `RIQ vIWAGO(B", (NAWTOBIOGRAFI^ESKAQ POWESTX (B"(Nl@DI I POLOVENIQ(B".s
rus
Keywords: (NsTIHOTWORENIQs